The satisfaction level of Muslim patients analysis toward Islamic dental health services - Agung Sosiawan, Aqsa Sjuhada Oki, Taufan Bramantoro, Aulia Nur Layli, (Opción, 2020)
The needs of Muslim patients regarding health services might be different from others, including needs in dental health services. To analyze the level of satisfaction of Muslim patients against Islam-based dental health services in Islamic dental clinics. The results showed that there were 11 elements in 5 dimensions of Seroquel that the performance of health care providers had met the interests of high patients. The Islam-based dental health services are good and need to be maintained by the health service providers. This can be the foundation of the Islamic-based dental health service standards.